2021
DOI: 10.3389/fmed.2021.749903
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of the Prognostic Nomogram to Predict Refractive Error in Patients With Primary Angle-Closure Glaucoma Who Underwent Cataract Surgery Combined With Goniosynechialysis

Abstract: Objective: To evaluate the accuracy of different intraocular lens (IOL) power calculation formulas and develop prognostic nomograms to predict the risk of postoperative refractive error in primary angle-closure glaucoma (PACG) patients.Methods: A total of 111 eyes with PACG underwent goniosynechialysis combined with phacoemulsification and IOL implantation were included. SRK/T, Barrett II, Hoffer Q, and Kane formulas were used to predict postoperative refraction. Prediction error (PE) and absolute predictive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…The Kane (-0.06 D) and Barrett II (-0.07 D) formulas had a mean PE close to zero, while the Hoffer Q (-0.26 D) and SRK/T (-0.21 D) produced significantly myopic outcomes. 28 Although SRK/T showed significantly more myopic outcomes among the four formulas in our study, the mean PE (-0.08 D) was closer to zero than in the study by Li et al 28 This difference may be due to the inclusion of eyes with PACG in the previous study.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The Kane (-0.06 D) and Barrett II (-0.07 D) formulas had a mean PE close to zero, while the Hoffer Q (-0.26 D) and SRK/T (-0.21 D) produced significantly myopic outcomes. 28 Although SRK/T showed significantly more myopic outcomes among the four formulas in our study, the mean PE (-0.08 D) was closer to zero than in the study by Li et al 28 This difference may be due to the inclusion of eyes with PACG in the previous study.…”
Section: Discussioncontrasting
confidence: 65%
“…A few studies have evaluated refractive results with different IOL formulas in combined cataract and glaucoma surgery. 26 , 27 , 28 Iijima et al 26 compared the accuracy of IOL power calculation using the SRK/T and Barrett-Universal II formulas in 56 eyes after combined trabeculectomy and cataract extraction and found that the Barrett provided a smaller absolute error. Marta et al 27 analyzed refractive errors in the Haigis, SRK/T, Holladay 1, Hoffer Q, Barrett-Universal II, Hill-RBF, and Kane formulas in combined cataract surgery and Ahmed glaucoma valve implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, discrepancies are unsurprising in IOL prediction in eyes with PACD. Additionally, currently available studies conducted among PACD eyes showed divergent accuracies of different formulas [7,9,21,[24][25][26]. All these facts stress the importance of our study.…”
Section: Discussionsupporting
confidence: 53%
“…severe pterygium, severe corneal or vitreous opacity, macular degeneration, and retinal detachment, etc. [21]); 3) preoperative ocular biometric measurements performed with instruments other than IOLMaster; 4) studies that did not provide targeted outcome data or that were computationally unavailable.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%